Assessing e-government implementation in an integrated personnel information system: a qualitative case study - Putu Angga Widyadinata; I.G.A.AG Dewi Sucitawathi Pinatih (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
The implementation of e-government has become an essential part of public sector reform in Indonesia, particularly in the management of civil service administration. However, many local government agencies still face difficulties in achieving effective digital integration, especially in personnel information systems. This study examines the implementation of the Integrated Personnel Information System (SIPETIR) at the Badung Regency Personnel and Human Resources Development Agency through the lens of the SPBE framework. The research employed a qualitative case study design involving 10 informants selected purposively from the agency’s leadership, administrators, IT staff, and employees. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model with the assistance of NVivo 14. The findings show that SIPETIR has improved the speed of administrative services, strengthened transparency in personnel processes, and reduced manual procedures in promotion, leave, and retirement services. However, the system still faces several challenges, including incomplete integration with SIASN, limited technical staffing, and delays in updating employee data, such as the case of employees who have not updated their personal records. Findings are limited to a single agency and may not generalize. The study suggests that the success of e-government implementation depends not only on digital infrastructure, but also on interoperability, continuous capacity building, and organizational commitment to data accuracy and service integration.